Pemanfaatan Media Flipbook dalam Meningkatkan Hasil Belajar Siswa Kelas V di SDN Sukoanyar Kediri - Muhammad Zidni Ilman Nafi'a; Moh. Hanif Adzhar (Dimar Jaya Publishing, 2026)
This study aims to determine the improvement in student learning outcomes on Changes in the State of Matter through flipbook learning media in the fifth-grade class at UPTD SDN Sukoanyar, Kediri. The study employed Classroom Action Research (CAR) over two cycles, with pretest and posttest data in each cycle used to analyze student progress. Results indicate improved learning outcomes from cycle to cycle. In the first cycle, the average pretest score was 78 with a mastery rate of 84%, while the average posttest score was 81 with a mastery rate of 94%. In the second cycle, the average pretest score rose to 81 with a mastery rate of 90%, and the average posttest score was 85 with a mastery rate of 97%. The analysis concludes that flipbook media consistently helped students understand the material, yielding a significant improvement in learning outcomes. These findings imply that flipbook media offers a practical, interactive strategy elementary teachers can adopt to strengthen students' grasp of abstract science concepts.